Derivation of a wear scar geometry-independent coefficient of friction from fretting loops exhibiting non-Coulomb frictional behaviour - Jin, X.; Sun, W.; Shipway, P.H. (Elsevier, 2016)
One source of variation of the sliding tractional force in a gross-slip fretting cycle is the geometrical interaction of the developing wear scars on the opposing specimens. An existing model has been developed to include the compliance of the fretting test apparatus. It has thus been demonstrated that through the influence on the tractional force, the geometrical development of the wear scars affects the slip amplitude and the dissipation of frictional energy in each loop. A method to determine a coefficient of friction which is independent of system stiffness and developments in the geometry of the wear scars is proposed.